Ecosystem management capabilities: development and mensuration of a scale - Farago, Fábio Emanuel (2023)
The complementarity and technological interdependence are central features of ecosystems. However, despite its relevance being widely recognized, it is still unclear how focal firms develop and manage complementarity and technological interdependence in ecosystems. While the current literature implicitly places these features as if it emerges automatically inside ecosystems, I propose that they need to be nurtured and managed by the focal firm through new ecosystem management capabilities. My main objective lies in the proposal of unveiling how focal firms develop complement arity and interdependence for ecosystem management through a capability lens. The methodology employed consisted of a qualitative and a quantitative phase. I started with an exploratory multiple case study in ten ecosystem focal firms, from which I proposed two new capabilities: the complementarity management capability and the technological management capability management capability. I described each capability with its own set of activities, definition, and measurement scale. The quantitative phase consisted of a survey with 275 executives. First, I used principal component factorial analysis, which resulted in the creation of two constructs for complementarity: i) ecosystem connections and ii) integration, and oth er two for technological interdependence: i) technological modularity and ii) co-development. Then, I applied structural equation modeling to validate the scales, which provided evidence to empirically support that the development of innovation can be associated with the development of the complementarity management capability and the technological interdependence management capability. These findings contribute to the capabilities-based view by showing a new type of capability that goes beyond the individual firm and considers its interaction with the ecosystem. For the ecosystem literature, this thesis contributes by presenting an understanding of how focal firms articulate the most central features of ecosystems into two new capabilities. Finally, I also contributed by developing and measuring two new constructs: a scale to measure complementarity and technological interdependence for focal firms